Work Environment Characteristics and Teacher Well-Being: The Mediation of Emotion Regulation Strategies - Yin, Hongbiao (Int J Environ Res Public Health, 2016)
Based on an adjusted Job Demands-Resources (JD-R) model that considers the mediation of personal resources, this study examined the relationships between two characteristics of teachers’ work environment (i.e., emotional job demands and trust in colleagues) and two indicators of teachers’ well-being (i.e., teaching satisfaction and emotional exhaustion). In particular, the study focused on how emotion regulation strategies (i.e., reappraisal and suppression) mediate these relationships. Data collected from a questionnaire survey of 1115 primary school teachers in Hong Kong was analyzed to test the hypothesized relationships. The results of structural equation modeling indicated that: (1) the emotional job demands of teaching were detrimental to teacher well-being, whereas trust in colleagues was beneficial; (2) both emotion regulation strategies mediated the relationships between both emotional job demands and trust in colleagues and teacher well-being; and (3) teachers who tend to use more reappraisal may be psychologically healthier than those tend to adopt more suppression. These findings support the applicability of the JD-R model to school settings and highlight the role of teachers’ emotion regulation in teachers’ well-being. Implications for the improvement of school environments and teachers’ well-being are identified.